Staggered prices and trend inflation: Some nuisances - Guido Ascari (Bank of Finland, 2003)
Most of the papers in the sticky-price literature are based on a log-linearization around the zero inflation steady state, a simplifying but counterfactual assumption.This paper shows that when trend inflation is considered, both the long-run and the short-run properties of DGE models based on the Calvo staggered price model change dramatically.It follows that results obtained by models log-linearized around a zero inflation steady state are quite misleading.Furthermore, the same is not true for models based on the Taylor staggered price model, which is robust to changes in trend inflation.As a conclusion, the Taylor model is to be preferred, unless one is willing to index nominal variables.
URN:NBN:fi:bof-20140807606
Keywords: 330